Bangladeshi Female Graduate Doctors Leaving Medical Profession: A Real Threat to Health System or a Rumor - Akhter, Najnin; Kabir Talukder, Md Humayun (Bangladesh Journal of Medical Education, 2025)
Background: Female graduate doctors represent a major part of health care/ educational services in Bangladesh. But a portion of female graduate doctors leaving their profession immediately or after sometimes of completion of their graduation, even some of them never registered themselves under Bangladesh Medical & Dental Council (BM&DC). Objective: This research aimed to find out percentages of female graduate doctors leaving medical profession and different reasons behind it. Methods: This cross sectional descriptive research was carried out in the Centre for Medical Education (CME), Mohakhali, Dhaka from July 2022 to June 2023. Data were collected through one self-administered semi-structured questionnaire among 500 female graduate doctors who got their registration from 2005-2020 and selected by convenient and snowball sampling. Results: Among 500 female graduate doctors, 428 (85.6%) were involved in different health care services and rest 72 (14.4%) were not involved and among rest 14.4%, about 10% never involved in health care services after completion of their graduation. When 72 respondents female graduate doctors who were not involved asked about their current professions, about one fourth (25%) mentioned they were doing ‘online businesses’, 15.02% were ‘purely housewife’ and 12.5% were ‘changing profession to others’. Among 72 respondents female graduate doctors, one third (33.33%) chose other profession for 'better income'. The most two common reasons for not involving were 'to care children' (39.7%) and 'absence of day care centers' (20.5%). Nearly half (45.5%) of the respondents chose 'establishment of day care / breast feeding centers' when they asked what strategies the government should take to utilize female work force effectively. Conclusions: Female graduate doctors who were not involved in health system mentioned different reasons behind their decisions and strategies require to be taken by the Government to overcome such conditions. BJME, Volume-16, Issue-01, January 2025: 15-25